Strings MM, University of Michigan : proceedings of the 2000 International Superstrings Conference, University of Michigan : University of Michigan, Ann Arbor, July 10-15, 2000 - Duff, M. J.; Liu, James T.; Lu, Jianxin (World Scientific, 2001)
Superstring theory and its successor, M-theory, hold promises of a deeper understanding of the Standard Model of particle physics, the unification of the four fundamental forces, the quantum theory of gravity, the mysteries of quantum black holes, Big Bang cosmology and, ultimately, their complete synthesis in a final theory of physics. This volume records the proceedings of the major annual international conference on the subject, "Strings 2000", which involved 42 talks by the world's leading experts on string theory and M-theory. It will be of interest not only to researchers in the field but also to all those who wish to keep abreast of the latest developments and breakthroughs in this exciting area of theoretical physics.